Analisis Faktor-Faktor yang Memengaruhi Pemahaman Privasi Informasi pada Pengguna Smartphone di XYZ dengan menggunakan Mobile User's Information Privacy Concerns (MUIPC) - Evi Oktavia Kurniawati; Ari Kusyanti; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Smartphone is a mobile that can facilitate users in interacting with other users. Nowadays, people can't spend a day without their smartphones due to increased productivity when using it. But, behind the development of information technology and telecommunications which seems favorable, on the other side this development can be done by the developers of smartphone by processing users's information which they obtain from the user's smartphone with their own policy without the knowledge of the user. This can be detrimental to users of the smartphone because they can't control the policies of information privacy that can be accessed by the developer. This research aims to analyze the factors that influenced the understanding of the information privacy of smartphone users at XYZ using the mobile user's information privacy concerns (MUIPC), this research used 8 latent variables and 26 manifest variables. The data was collected from the active smartphone users with the age ranged above 17 years old at XYZ with 278 respondents. Data analysis methods that used is Structural Equation Modeling (SEM). From the results, showed that factor understanding of the privacy information on smartphone users at XYZ was influenced by the variables Prior Privacy Experience, Secondary Use of Personal Info, Perceived Surveillance, and Perceived Intrusion.